THE ROLE OF ORGANIZATIONA JUSTICE IN FOSTERING ORGANIZATIONAL CTIZENHIP BEHAVIOUR: A STUDY AT A MULTINATIONAL BANK IN INDONESIA - Hilmaya Puspa Dania; Dewi Lusiana (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study investigates the influence of organizational justice on organizational citizenship behaviour (OCB) among employees at PT Bank DBS Indonesia. Drawing on Social Exchange Theory, the research explores how perceptions of fairness in outcomes, procedures, and interpersonal interactions drive employees’ willingness to go beyond formal job responsibilities. Using a quantitative survey method and Partial Least Squares Structural Equation Modeling (PLS-SEM), the study finds that organizational justice has a significant positive effect on both individual-directed OCB (OCBI) and organization-directed OCB (OCBO). These findings highlight the importance of fair treatment in promoting supportive, proactive, and loyal behaviors among employees—especially within the high-pressure, innovation-driven environment of digital banking. The study offers practical implications for managers in cultivating a fair workplace climate to foster employee engagement and long-term organizational success.